2011
DOI: 10.1111/j.1574-6968.2011.02231.x
|View full text |Cite
|
Sign up to set email alerts
|

UV-resistant Acinetobacter sp. isolates from Andean wetlands display high catalase activity

Abstract: Andean wetlands are characterized by their extreme environmental conditions such as high UV radiation, elevated heavy metal content and salinity. We present here the first study on UV tolerance and antioxidant defense of four Acinetobacter strains: Ver3, Ver5 and Ver7, isolated from Lake Verde, and N40 from Lake Negra, both lakes located 4400 m above sea level. All four isolates displayed higher UV resistance compared with collection strains, with Ver3 and Ver7 being the most tolerant strains not only to UV ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…Other studies investigating differences in UV survivorship have focused on bacteria isolated from one particular type of environment, such as high-altitude lakes or other extreme environmental conditions (Fernández Zenoff et al, 2006). In one such study, a novel A. johnsonii strain designated A2 was isolated from Andean wetlands and was found to be significantly more resistant to UV-B than A. johnsonii ATCC 17909 T (Di Capua et al, 2011), which we also observed to be very sensitive to UV-C radiation. Our observation that A. radioresistens is highly UV-C resistant compared with other Acinetobacter strains is consistent with previous findings that A. radioresistens is four-to eightfold more resistant to gamma radiation (Saha & Chopade, 2009) and~28-fold more resistant to ionizing radiation (Nishimura et al, 1994) than a limited set of other Acinetobacter strains, although the range of difference in survival was significantly greater (~300 000 fold) in this study than in these previous works.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies investigating differences in UV survivorship have focused on bacteria isolated from one particular type of environment, such as high-altitude lakes or other extreme environmental conditions (Fernández Zenoff et al, 2006). In one such study, a novel A. johnsonii strain designated A2 was isolated from Andean wetlands and was found to be significantly more resistant to UV-B than A. johnsonii ATCC 17909 T (Di Capua et al, 2011), which we also observed to be very sensitive to UV-C radiation. Our observation that A. radioresistens is highly UV-C resistant compared with other Acinetobacter strains is consistent with previous findings that A. radioresistens is four-to eightfold more resistant to gamma radiation (Saha & Chopade, 2009) and~28-fold more resistant to ionizing radiation (Nishimura et al, 1994) than a limited set of other Acinetobacter strains, although the range of difference in survival was significantly greater (~300 000 fold) in this study than in these previous works.…”
Section: Resultsmentioning
confidence: 99%
“…B. subtilis spores) [22], (ii) high catalase activity (Acinetobacter sp.) [9], (iii) sodium chloride concentrations in biofilm (Listeria monocytogenes) [3], (iv) biofilm formation (P. aeruginosa) [10], and (v) nucleotide excision repair by the uvrABC complex (Mycobacterium smegmatis) [19]. Considering the possibility that UV-tolerant bacteria could be present in the environment, such as P. aeruginosa, A. baumannii and B. cereus, as previously described, the pulsed UV radiation is a sufficient UV irradiation dose for disinfection of the environment.…”
Section: Environmental Disinfection Using Pulsed Uv Radiationmentioning
confidence: 97%
“…However, pyocyanin showed no growth inhibition of A. baumannii (MIC Ͼ 18 mM), as it counteracted the pyocyanin-mediated oxidative stress by enhanced production of catalase and SOD. A. baumannii has been reported to combat H 2 O 2 -generated oxidative stress by increasing its catalase activity (32). Pyocyanin exerts oxidative stress on P. aeruginosa cells also, but it survives because of limited redox cycling of pyocyanin and increased levels of catalase and SOD (7).…”
Section: Discussionmentioning
confidence: 99%